Chapter The Edict Issued by the Hittite King Ḫattušili III Concerning the Priesthood of the Goddess Ištar/Šaušga - DE MARTINO, Stefano (Studia Asiana, 2023)
This essay presents an updated edition of the Hittite document KBo 6.29+. This text is a royal edict issued by Ḫattušili III and establishes that the sanctuary of the Goddess Šaušga will be exempted from any levies. The regulations concerning this sanctuary are preceded by a long introduction where the king relates his conflict with Urḫi-Teššob. This presentation can be compared with the narrative on this event that is documented in the 'Apology.'